(untitled) (Bangladesh Journal of Medical Science, 2024)
Background and Aim: Brachial plexus blocks (BPB) are indispensable in providing surgical anaesthesia and postoperative analgesia. Although Hemi-diaphragmatic palsy (HDP) after BPB is clinically insignificant in the majority, it can cause significant physiological impairment in patients with reduced pulmonary function. Sonographic assessment of diaphragmatic function using the ABCDE approach provides accurate and quantitative information on HDP. This can be performed bedside before and after administration of the nerve block to quantify HDP. This was a prospective observational study comparing ultrasound-guided diaphragmatic thickness in two approaches of ultrasound-guided BPB. Methodology: Eighty participants receiving eitherinterscalene/supraclavicular BPB were included in this observational study. Baseline vitals, NRS score for pain and ultrasound-guided diaphragm thickness at inspiration and expiration using the ABCDE approach were noted. After 20 minutes of BPB administration, the diaphragm thickness was remeasured. Results: Eighty participants completed the study, forty from either group. Average volume of the total local anaesthetic drug mixture used was noted to be 30ml. The diaphragmatic thickness ratio in the supraclavicular group was found to decrease by 2.34% as compared to 2.39% in the interscalene group. (p-value 0.256 baseline values,0.292 for post block values) The thickness fraction was found to decrease by 9.21% in Group A as compared to 9.04% in Group B (P value 0.248 baseline values and 0.292 post-block values). There was no statistically significant difference between the diaphragm thickness in both the group’spre- and post-block, irrespective of the approach used. Conclusion: The ABCDE approach to measure diaphragm thickness can be used as a simple bedside modality to quantify the amount of HDP occurring after ultrasound-guided BPB. It is easy to learn & a non-invasive modality which can be used to improve patient safety during BPB Bangladesh Journal of Medical Science Vol.23 (Special Issue) 2024 p.S101-S106